Would the elimination of obesity and smoking reduce U.S. racial/ethnic/nativity disparities in total and healthy life expectancy? - Michelle L. Frisco; Jennifer Van Hook; Robert A. Hummer (Elsevier, 2019)
Obesity and smoking are the two leading causes of preventable death and disability in the United States. Both of these health risks are socially patterned in ways that likely produce racial/ethnic/nativity disparities in total and healthy life expectancy. The current study simulates the extent to which the hypothetical elimination of smoking and obesity would change disparities in longevity and disability by analyzing data from 19,574 U.S.-born white, black, Hispanic and foreign-born Hispanic men and women in the 1999-2000 through 2009-2010 National Health and Nutrition Examination Survey and linked mortality files. Results suggest that the elimination of both obesity and smoking would significantly narrow disparities in total and healthy life expectancy between black and white adults and remaining differences are statistically non-significant. The longstanding life expectancy advantage of Hispanic immigrants over whites is reduced, but remains large. The life expectancy advantage of U.S.-born Hispanics is reduced as well, though to a smaller extent than what is observed for Hispanic immigrants. There were no significant observed healthy life expectancy differences between white and U.S.-born Hispanic adults. Overall study results suggest that the elimination of obesity and smoking would change the shape of racial/ethnic/nativity disparities in ways that would result in greater health equity. Keywords: Epidemiological paradox, Obesity, Smoking, Racial disparities, Mortality, Healthy life expectancy